ANALISIS PRODUK DOMESTIK BRUTO, NILAI PERUSAHAAN, DAN RISIKO SISTEMATIS TERHADAP RETURN SAHAM PERUSAHAAN INDEKS KOMPAS100 - Himawan Rahardika (2022)
This study was conducted to determine the effect of Gross Domestic Product (GDP), firm value and systematic risk on the stock returns of the company listed in the Kompas100 index. The population in this study is the Kompas100 Index company on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. The sampling technique used was purposive sampling and 53 companies with the Kompas100 index were used as research samples. Data analysis used Panel Data Regression Analysis using Eviews 12 with significance level of 5%. The results showed that Gross Domestic Product (GDP) and systematic risk (beta) had a negative effect on stock returns, while firm value had no effect on stock returns of the Kompas100 index company.